Maize NAC-domain retained splice variants act as dominant negatives to interfere with the full-length NAC counterparts. (December 2019) - Zhang, Jie; Li, Liang; Huang, Liping; Zhang, Manman; Chen, Ziyan; Zheng, Qingsong; Zhao, Haiyan; Chen, Xi; Jiang, Mingyi; Tan, Mingpu
Highlights: Cd-induced intron retention splice NAC variants which only retained the canonical NAC domain. nacDomain interacts antagonistically with NAC as hetero-dimer to interfere with the full-length NAC counterpart. nacDomain functions as the dominant negative of the coupled NAC transcription factor. Abstract: The plant-specific NAC transcription factors play diverse roles in various stress signaling. Alternative splicing is particularly prevalent in plants under stress. However, the investigation of cadmium (Cd) on the differential expression of the splice variants of NACs is in its infancy. Here, we identified three Cd-induced intron retention splice NAC variants which only contained the canonical NAC domain, designated as nacDomains, derived from three Cd-upregulated maize NACs. Subcellular localization analysis indicated that both nacDomain and its full-length NAC counterpart co-localized in the nucleus as manifested in the BiFC assay, thus implied that nacDomains and their corresponding NACs form heterodimers through the identical NAC domain. Further chimeric reporter/effector transient expression assay and Cd-tolerance assay in tobacco leaves collectively indicated that nacDomain-NAC heterodimers were involved in the regulation of NAC function. The results obtained here were in accordance with the model of dominant negative, which suggested that nacDomain act as the dominant negative to antagonize the regulation of NAC on its target gene expression and the Cd-tolerance function performance of NAC transcription factor. These findings proposed a novel insight into understanding the molecular mechanisms of Cd response in plants.